Pengaruh Quality of Work Life, dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan Kantor Unit Pelayanan Sako Kenten PDAM Tirta Musi Palembang - Rizky Amalia; Farla, Wita; Yos Karimudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine or analyze the effect of quality of work life and work motivation on employee job satisfaction. This research uses quantitative methods. The population in this study were employees of the Sako Kenten Service Unit Office of PDAM Tirta Musi Palembang. The sample used is saturated sampling so that the sample in this study is the entire population of employees of the Office of the Sako Kenten PDAM Tirta Musi Palembang Service Unit, totaling 36 respondents. This study used primary data obtained through questionnaires and multiple linear regression analysis as a data analysis technique. Based on the results of the hypothesis analysis, it was concluded that partially the quality of work life has a significant effect on employee job satisfaction while work motivation has a insignificant effect on employee job satisfaction. However, in a simultant way, quality of work life and work motivation have a significant effect on employee job satisfaction at the Sako Kenten Service Unit Office, PDAM Tirta Musi, Palembang.